Efficacy of Phenobarbital and Prognosis Predictors in Women With Epilepsy From Rural Northeast China: A 10-Year Follow-Up Study - Chu, Chaojia; Li, Nan; Zhong, Rui; Zhao, Danyang; Lin, Weihong (Frontiers in Neurology, 2022)
Objective: To investigate the efficacy of phenobarbital (PB), factors associated with it, reasons for early treatment termination, and mortality rates in adult women living in rural Northeast China. Methods: A prospective study was conducted in seven counties of Jilin Province from 2010 to 2020. Adult women diagnosed with convulsive epilepsy were recruited into the study and baseline demographics recorded upon enrollment. Seizure frequency, prescribed drug dose, and adverse reactions were monitored monthly by door-to-door survey or telephone interview. Results: A total of 1333 women were included in the study. During the follow-up period, 169 participants (12.7%) were lost to follow-up, and 100 of them (7.5%) died. The percentage of seizure-free participants was 45.3% in the first year, 74.6% in the third year, and 96.6% in the 10th year. A higher baseline seizure frequency (OR=1.005, 95% CI: 1.002-1.009), more frequent loss-of-consciousness seizures (OR=1.620, 95% CI: 1.318-1.990), a higher daily dose of PB in the first year (OR=1.018, 95% CI: 1.014-1.022), a younger age at onset (OR=0.990, 95% CI: 0.982-0.998), and more severe drowsiness (OR=1.727, 95% CI: 1.374-2.173) were associated with an increased risk of seizures in the first year, and the higher baseline seizure frequency was still associated with the occurrence of seizures in the third (OR=1.007, 95% CI: 1.004-1.010) and fifth year (OR=1.005, 95% CI: 1.002-1.008). Age at enrollment (HR=0.983, 95%CI: 0.971-0.994) was the only factor that correlated with withdrawal from the study and with death of the participant during the follow up period, but the correlation in each case was in opposite directions. Significance: PB has a high effectiveness, retention rate, mild side effects, and tolerability when used as treatment for epilepsy in women from rural areas. Baseline seizure frequency is an important predictor of prognosis regardless of treatment duration. PB is still a valuable tool for the management of epilepsy in adult women from poverty-stricken areas.